The Leadership Role of Principals, Teachers, and Educational Personnel in Developing a Quality Culture in Islamic Educational Institutions - Ardiansyah, Moch Verry; Sa’adah, Salma Fatimatus; Fitriani, Belliana Rahma (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
The purpose of this article is to explain the concept of quality culture in educational institutions, the role of principals, teachers, and education personnel in building a quality culture, as well as the obstacles and solutions in its implementation. Quality culture is a value system oriented towards improving the quality of education continuously by involving all elements of the school. The principal plays a strategic role in planning, supervision, and motivation; teachers play a role as implementers of quality culture through effective and character-based learning; while education personnel support the creation of an orderly and conducive school environment. However, the implementation of quality management in educational institutions still faces various obstacles such as a lack of understanding of the concept of quality, low teacher quality, limited funding, curriculum inconsistencies, and minimal support from related parties. To overcome these, strategies are needed such as improving the competence of educators, developing an integrated curriculum, effective communication, regular self-evaluation, and collaboration between schools, the government, and the community. The research method used is a literature study by collecting various sources such as books, journals, and related scientific articles. The results of the study indicate that the consistent and collaborative implementation of quality culture can improve the quality of education and shape students with character and high competitiveness.